Filosofia e ensino médio integrado do campus Óbidos do instituto federal do Pará: uma relação pautada na formação humana integral - Sena, Erika Viana de (2021)
The Integral Human Formation (IHF) is a fundamental concept of Professional and Technological Education (PTE). The research development took place at Campus Óbidos of Instituto Federal do Pará, among students from System Development Technical Course. The main goal on this research is to understand how Philosophy can contribute on Integral Human Formation of students from Integrated High School (IHS). The path we follow to achieve the goal was explaining IHF concept, discussing the importance from IHF to HIS, comparing the goals from Philosophy learning to IHF, and verify within students perspective the achievement of IHF on their scholar experience. The tools used to data collet were electronic questionnaire, online focus group, and journal. The data analysis was done using Phenomenology method. It helps understanding facts and considers subjectivity as an important element on reality interpretation. We expect to demonstrate the importance of Philosophy to Integral Human Formation on students perspective. We could see from students speech that both Philosophy and humanities subjects are important to achieve Integral Human Formation and during our interactions we developed an Educational Product named Shal I draw it? Explaining IHF through stripes as a material to help other students to achieve good results on IHF even in other humanities subjects and contexts. The message transmitted on this Comic book is significant once it represents students voice that care and contribute to other students formation.